Comprehending conjunctive entailment of disjunction among individuals with Asperger syndrome. (2nd September 2019) - Liu, Chin-Ting; Chen, Li-Mei
ABSTRACT: Although individuals with Asperger syndrome (AS) are often described to be semantic-pragmatic disordered, it is still unclear to what extent their semantic comprehension is impaired. The primary goal of this study is to understand the sentence comprehension of adults with AS by investigating their reading processes of sentences involving the conjunctive entailment of disjunction. More specifically, their on-line processes of reading globally ambiguous sentences containing huo 'or' in Mandarin Chinese, which can be understood as either a conjunction or a disjunction in simple negative statements, were recorded. The results indicated that both AS and typically developing groups tended to interpret the ambiguous huo as a conjunction. Additionally, both groups consistently spent significantly more time judging the appropriateness of disjunction-biased sentences. It is argued that, for adults with AS, at least some aspects of semantic knowledge are intact. Future studies are suggested to focus on different sentence types to further explore to what extent that semantics is impaired among individuals with AS.